The peculiarities of the conceptual approach to pre-translation analysis (Eurasian Journal of Philology Science and Education, 2016)
The integration of the modern society into the global political, economic and cultural space is in need of qualified translators with a high level of professional competence. In this connection the question arises about the necessity to improve the quality of translated texts. This article is devoted to the problems of pre-translation analysis. The article discusses various conceptual approaches to the problem of pre-translation analysis, the authors share their opinions and have their own point of view on this issue, and they also offer a scientific solution. The importance of the topic is due to the fact that the in-depth study of this problem will facilitate cross-language communication and make translation more appropriate, since an adequate understanding of meaning is the basis of all types of translation. This article does not question the three-stage structure of the translation process, comprising the steps of perception and understanding of the original text, the translation stage, the stage of editing and analyzing the results of the translation.
Keywords: quality of translation; pre-translation analysis; translation strategy; type of information; conceptual approach.